Determinants of Entrepreneurship: An Examination of Entrepreneurial Perception of Students - Cristina-Lidia Manea; Elena-Mirela Nichita; Alina Mihaela Irimescu (Journal of Accounting and Management Information Systems (JAMIS), 2019)
Research Question: What determinants drive the entrepreneurial intentions of students enrolled in accounting master programs: entrepreneurial competencies, family and friends support or entrepreneurial education? Motivation: The current research purpose is to explore to what extent the entrepreneurship is a feasible alternative career for students enrolled in accounting master programs and the role of academic education in entrepreneurship in selecting the entrepreneurial career. Generally, entrepreneurs are associated with providers of novel products and/or services, but we consider the entrepreneurial career in accounting services as feasible as any other career. Idea: The student's interest in entrepreneurial activities remains greatly influenced by the entrepreneurial universities policies, making the role of universities crucial. Based on the affirmation that current students will be tomorrow's successful entrepreneurs (Pribeanu and Milutin, 2014), it is essential to increase the impact of entrepreneurial education on the student's life. It is not easy for universities, knowing the changes and challenges that they have to face nowadays (Schulte, 2014), but it is their responsibility and they do have the responsibility to make the change possible. Data: The data of this paper is collected based on a survey on the student's perception on entrepreneurship and analyses the competences and abilities they gain as result of their bachelor studies and how these perceived competencies and abilities are currently helping or will help them to choose an entrepreneurial career. Tools: The study is based on a questionnaire distributed to master students enrolled in accounting master programs organized by The Bucharest University of Economic Studies. The research methodology consists of a descriptive analysis and regression analysis. Additionally, the structure of questionnaire allows us to use the Carlsson et al.'s (2012) framework for investigating the entrepreneurship, which is based on two perspectives, namely explorative and exploitative. Findings: The findings allow to state that students are taking into consideration the entrepreneurship career and their decision is positively influenced by family and friends setting and education. The test of the models resulted in adjusted R-squares higher than 0.90 indicating robust support for the regression models. Contribution: Our empirical study investigates three determinants of entrepreneurial skills and, as result of this research, universities, government officials and others interested in stimulating entrepreneurial motivation should consider how their actions affect potential entrepreneurs' enthusiasm. Furthermore, this academic paper enhances the Romanian academic literature in the field of entrepreneurship.
Keywords: I25; M41; 650; entrepreneurship; willingness to become an entrepreneur; family support; entrepreneurial skills; entrepreneurial education